PERBAIKAN MANAJEMEN PAKAN DENGAN PENGGUNAAN LIMBAH PERTANIAN PADA USAHA PETERNAKAN BABI DI DESA KUTA, KECAMATAN KANATANG, KABUPATEN SUMBA TIMUR - Hambakodu, Marselinus; Pari, Aris Umbu Hina; Kata, Santrialensi Rambu (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The problem faced by pig farmers in Kuta Village, Kanatang District, East Sumba Regency in raising pigs was productivity and long rearing time. The cause of this problem was the high cost of feed due to relying on commercial feed which is relatively expensive and continues to increase. Community service activities are carried out for 1 month, namely from 01 to 30 November 2022. The purpose of this community service was to improve the management of pig feed in Kuta Village, Kanatang District. The community service method used socialization and counseling, problem identification, training implementation, monitoring and evaluation, and mentoring. The solution offered to pig farmers was to improve the management of raising pigs, namely a) how to process agricultural waste (banana stems and rice bran) into alternative feed ingredients, b) how to make rations and mix them into fermented feed, c) how to manage the environment of the cage and how to feeding. The evaluation carried out is the success rate of making feed, how to feed it, and managing the environmental health of the cage. The result of the Community Service Program that has been carried out was an increase in skills in raising livestock and providing quality feed that was economical.